Kinetic analysis of Toe-on Tkachev on uneven bars - Kerwin, D. G.; Irwin, G. (ISBS - Conference Proceedings Archive (Konstanz), 2011)
The purpose of this study was to explain the mechanics of the Toe-on Tkachev on Uneven Bars, and to identify how the release conditions were created. 3D video based data and inverse dynamics were used to analyze five different Toe-on Tkachevs recorded at the 2007 World Championships. Digitising and DLT techniques were combined with customised inertia modelling as input to standard inverse dynamics. Data were normalised to eliminate influences of height and mass. Hip action was characterised by a single large input which peaked close to the horizontal on the upswing, followed by a smaller negative shoulder power contribution as release was approached. The dominant role of positive hip extension was highlighted as a major factor contributing to the creation of the final body orientation and desirable release conditions.